Comprehensive energy, exergy, and environmental evaluation of integrated heat pipe photovoltaic/thermal systems using multi-objective optimization - Ghasempour, Roghayeh; Salehi, Mohammad; Fakouriyan, Samaneh (Applied thermal engineering, 2024)
•Exergy, energy, and environmental analysis of PV/T systems based on heat pipes.•Comparing PV/T performance of thermosyphon & pulsating heat pipe with water/acetone.•Maximizing exergy of PV/T systems using MOPSO and NSGA II optimization algorithms.•Thermosyphon heat pipes with acetone boost PV panel exergy by 14.2 %.•PV/T systems with heat pipes cut GHG emissions by up to 894.5 kg/year·m2. The depletion of fossil fuels and their environmental emissions have led to a tendency toward the implementation of sustainable energy sources. This study aims to evaluate the energy, exergy, and environmental performance of photovoltaic/thermal systems-based heat pipes. Furthermore, the electrical exergy and thermal efficiency of the photovoltaic/thermal system are analyzed. In this regard, two methods of multi-objective evolutionary algorithm based on non-dominated sorting genetic algorithm II (NSGA II) and multi-objective particle swarm optimization (MOPSO) are utilized. The simulated heat pipes are regarded as thermosyphon and pulsating type with water and acetone as the working fluid. The novelty of this study lies in the comparative analysis of thermosyphon and pulsating heat pipes with water and acetone as working fluids in PV/T systems, combined with the application of advanced multi-objective optimization algorithms, offering a comprehensive. The result demonstrates that acetone, as a working fluid, can help achieve better performance compared towater, and also pulsating heat pipe illustrates greater performance rather than the thermosyphon heat pipe. Moreover, the result reveals that the electrical exergy efficiency of the photovoltaic panel equipped with thermosyphon heat pipe with acetone has increased by 14.2 % compared to the photovoltaic panels without the heat pipe. In addition, utilizing thermosyphon base photovoltaic/thermal system with acetone reduces the production of greenhouse gases by 894.5 CO2eqkg/m2.year, which is a further reduction of 156.8 CO2eqkg/m2.year compared to the photovoltaic panel without a heat pipe.